Modified Two-Step Dimethyl Ether (DME) Synthesis Simulation from Indonesian Brown Coal - Sasongko, Dwiwahju; Luthan, Abdurrahman Fadhlil Halim; Wulandari, Winny (ITB Journal Publisher, LPPM ITB, 2016)
A theoretical study was conducted to investigate the performance of dimethyl ether (DME) synthesis from coal. This paper presents a model for two-step DME synthesis from brown coal represented by the following processes: drying, gasification, water-gas reaction, acid gas removal, and DME synthesis reactions. The results of the simulation suggest that a feedstock ratio of coal : oxygen : steam of 1 : 0.13 : 0.821 produces the highest DME concentration. The water-gas reactor simulation at a temperature of 400Â°C and a pressure of 20 bar gave the ratio of H2/CO closest to 2, the optimal value for two-step DME synthesis. As for the DME synthesis reactor simulation, high pressure and low temperature promote a high DME concentration. It is predicted that a temperature of 300Â°C and a pressure of 140 bar are the optimum conditions for the DME synthesis reaction. This study also showed that the DME concentration produced by the two-step route is higher than that produced by one-step DME synthesis, implying that further improvement and research are needed to apply two-step DME synthesis to production of this liquid fuel.